Integrasi Literasi Budaya dan Kewargaan Melalui Media Sosial pada Generasi Z di Era Digitalisasi - Amelia, Diaz Putri; Dewi, Dinie Anggraeni; Hidayat, Rizky Saeful (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Changing times are increasingly developing into a decline in cultural and civic literacy in the younger generation. Cultural and civic literacy is the ability to adapt to the culture of other countries who come to Indonesia but still instill a sense of love for the homeland by studying and understanding various Indonesian cultures. The modern generation Z needs to be closer to Indonesian culture which is adapted to the characteristics of generation Z. The aim of this research is to find out how to integrate cultural literacy and citizenship through social media in generation Z in the era of digitalization. This research method uses a literature study or literature review where the researcher uses secondary data obtained from journals, ebooks, and articles with the stages of planning, data collection, analysis, and synthesis. The research results show that the use of technology in the era of digitalization as a media platform for generation Z can increase cultural literacy and citizenship. One of them is a short video broadcast on the TikTok application. The integration of cultural and civic literacy in generation Z in the era of digitalization involves a deep understanding of the digital context.